The options doctor : - Young, Jeanette Schwarz (John Wiley & Sons, 2007)
The Options Doctor is Young's hands-on, practical guidebook for using options combined with technical analysis tools to both create and protect portfolio profits in every market environment. Covering topics from basic to advanced, and filled with entertaining, first-person stories from Young's career spent on the front lines of trading, it will improve your skill and comfort with options trading-whether you are a first-year trader still learning the ropes or a seasoned veteran looking for proven tips and tricks to jump-start your trading performance